Tetraazaacenes containing four-membered rings in different oxidation states: Are they aromatic? : a computational study - Schaffroth, Manuel; Bunz, Uwe H. F. (The journal of organic chemistry, 2014)
A symmetrical tetraazaacene incorporating a central cyclobutadiene ring was calculated in different oxidation (hydrogenation) states, displaying different tautomers and conformers. Geometries, thermodynamics, and electronic properties were computed, and the aromaticity of all these species was calculated on a per ring basis by NICS-scans and NICS-X-scans. The results unveil unexpected and fascinating insights into the complex aromaticity of those compounds, including a formally aromatic (!) cyclobutadiene ring.
Gesehen am 05.11.2020